PERANCANGAN BUKU INTERAKTIF MENGENAL KONSEP WAKTU DAN JAM UNTUK ANAK USIA DINI - Nadindra Ayu Arjani; Octavia, Ercilia Rini (SNADES, 2025)
Early childhood education is the most basic stage in building a child’s cognitive, emotional, and social foundation. Started as early as 4 years old, children would start to learn the concept of time, and as they grow older, they would also learn how to read clocks. However, learning time and reading clocks could feel a bit tiring and hard to follow for children at that age. To understand concepts that may be difficult for children of that age to digest, it is necessary to use real situations that can be easily understood by children. Additional media, such as real clocks, or other learning methods may be needed to help children understand the concept of time and clocks. Educational media such as interactive books would require the children to be active in learning. The design of this interactive educational book is expected to help children learn the concept of time and how to read clocks in a fun yet informative way.